The Effect of Granules of Spring Onionâs Extract (Allium fistulosum L.) to the Mortality of Anopheles aconitus Larvae - Saputra, Riko; Haryati, Sri; Wicaksono, Bagus (Nexus Biomedika, 2015)
Background: Nowadays the prevalence of malaria in Indonesia is still high. Anopheles aconitus is one of the vector of malaria. Insecticide is a way which government usesÂ to kill the Anopheles aconitus mosquitoes, but it can cause the resistence of the mosquitoes, because of that we need an alternative way to kill them, and we can use larvacide to kill the Anopheles aconitus larvae. Spring Onion contains substances that can be larvacide, so the researcher wanted to prove that granules of Spring Onionâs extract had effects to kill the Anopheles aconitus larvae. Methods:This research used laboratory experimental design with post test only control group design. The subject of this research was Anopheles aconitus larvae that were divided into 7 groups, each group contained 25 larvae and the research was repeated in 4 times. For the negative control group we used 100 ml water. The other six groups contained a different number of granules of Spring Onionâs extract; they were 850 mg, 1000 mg, 1150 mg, 1300 mg, 1450 mg, and 1600 mg. The observation was held after 24 hours, then, the number of dead larvae was counted. The data were analyzed using Linear Regression and Probit test. Results:Linear Regression test showed that the R correlation score was 0.984 and R2 score was 0.969, this meant that the effect of the number of granules of the Spring Onionâs extract to kill larvaes was 96.9% and the rest 3.1% was effected by the others variables. Probit test showed LC50 (Lethal Concentration) was 820.573 mg and LC99 was 1671.886 mg. Conclusion:There is effect of granules of Spring Onionâs extract to the mortality of Anopheles aconitus larvae. The LC50 is 820.573 mg and the LC99 is 1671.886 mg, while the effect of the number of granules to influence is R2: 96.9% and the correlation between the number of granules and mortality is R: 0.984. Keyword: granules, Spring Onionâs extract, Anopheles aconitus larvae, mortality